Long-term Outcomes of PreserFlo MicroShunt versus XEN45 Gel Stent in Open-Angle Glaucoma - Nobl, Matthias; Freissinger, Sigrid; Rudolph, Katrin; Vounotrypidis, Efstathios; Kassumeh, Stefan; Priglinger, Siegfried; Mackert, Marc Julian (Klinische Monatsblätter für Augenheilkunde, 2023)
Purpose To compare two glaucoma drainage devices with subconjunctival filtration (MicroShunt and XEN) for open-angle glaucoma (OAG), with respect to effectiveness and safety.Patients and Methods This is a single center, retrospective, interventional study. In total, 106 eyes of 95 patients with OAG underwent surgery. Of these patients, 51 eyes of 45 patients received a MicroShunt implantation and 55 eyes of 50 patients received an XEN implantation. Failure was defined as an intraocular pressure (IOP) lower than 5 or higher than 17 mmHg at the end of follow-up after 2 years, the need for surgical revision, secondary glaucoma surgery, or loss of light perception. Outcome was rated as complete success or qualified success, depending on whether it was achieved with or without anti-glaucomatous medications. Postoperative complications and interventions were also documented for both groups.Results In the MicroShunt group, mean IOP decreased from 20.6 ± 7.5 mmHg at baseline to 13.0 ± 3.9 mmHg (p < 0.0001) after 2 years. In the XEN group, mean IOP was lowered from 22.5 ± 7.9 mmHg to 13.5 ± 4.2 mmHg (p < 0.0001). In both groups, the mean number of medications was significantly reduced (MicroShunt 2.7 ± 1.2 to 0.9 ± 2.5; p < 0.0001 vs. XEN 3.2 ± 0.9 to 1.1 ± 1.5; p < 0.0001). In regard to success rates, 37% of MicroShunt patients achieved complete success and 57% qualified success at the end of follow-up. In the XEN group, rates were 25 and 45%, respectively. Patient demographics differed between the two groups with respect to age (MicroShunt 72.8 ± 8.7 vs. XEN 67.7 ± 9.0 years; p = 0.002). Postoperative complications were comparable between the two groups.Conclusion Both MicroShunt and XEN are effective in significantly reducing IOP and glaucoma medications in OAG, and with a good safety profile.
Keywords: choroid; conjunctiva; glaucoma